Evolución del sector turismo y su incidencia en el crecimiento económico del departamento de Boyacá durante el periodo 2000-2016 (2020)
The objective of this study is to verify the evolution of the tourism sector in the economy of the Department of Boyacá, as well as its impact on the economic growth of the Department. In order to cover the problem question, it is sought to examine what has been the evolution of the sector in the department through the projects proposed during each government through the development plans and from these assess the relevance of the tourism sector in the economic growth of the Department of Boyacá during the period 2000-2016.